Lipid Production From Waste Materials in Seawater-Based Medium by the Yeast Yarrowia lipolytica - Dobrowolski, Adam; Drzymała, Katarzyna; Rzechonek, Dorota A.; Mituła, Paweł; Mirończuk, Aleksandra M. (Frontiers in Microbiology, 2019)
The global limitation of fossil fuels impels scientists to search for new energy sources. A good alternative is biodiesel produced from crop plants. However, its production requires huge quantities of farmland, fertilizers and fresh water, which is in conflict with the human demand for water for consumption and land for food production. Thus, production of single cell oil (SCO) by oleaginous microorganisms remains the best solution for the coming years. Whereas most microorganisms require fresh water for proper cell metabolism, the unconventional yeast Yarrowia lipolytica is able to produce huge quantities of fatty acid in seawater-based medium. Here we demonstrate that Y. lipolytica is able to produce fatty acids in medium based on seawater and crude glycerol as the main carbon source, which allows for low-cost production of SCO, is beneficial for industrial application and is ecologically friendly.